2023
DOI: 10.1038/s42003-023-04806-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stimulation controls osteoclast function through the regulation of Ca2+-activated Cl− channel Anoctamin 1

Abstract: Mechanical force loading is essential for maintaining bone homeostasis, and unloading exposure can lead to bone loss. Osteoclasts are the only bone resorbing cells and play a crucial role in bone remodeling. The molecular mechanisms underlying mechanical stimulation-induced changes in osteoclast function remain to be fully elucidated. Our previous research found Ca2+-activated Cl− channel Anoctamin 1 (Ano1) was an essential regulator for osteoclast function. Here, we report that Ano1 mediates osteoclast respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It has been reported that LIPUS stimulation increases prostaglandin E 2 (PGE 2 ) secretion from osteoblasts, which inhibits osteoclast formation [ 30 ]. More recently, a mechanosensitive calcium-activated chloride channel, anoctamin-1 (Ano1), was downregulated in response to mechanical stimulation in osteoclasts and inhibited their activity [ 31 ]. Taken together, it is likely that LIPUS may directly and indirectly inhibit osteoclasts through Ano1 and osteoblast PGE 2 production, respectively, that will be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that LIPUS stimulation increases prostaglandin E 2 (PGE 2 ) secretion from osteoblasts, which inhibits osteoclast formation [ 30 ]. More recently, a mechanosensitive calcium-activated chloride channel, anoctamin-1 (Ano1), was downregulated in response to mechanical stimulation in osteoclasts and inhibited their activity [ 31 ]. Taken together, it is likely that LIPUS may directly and indirectly inhibit osteoclasts through Ano1 and osteoblast PGE 2 production, respectively, that will be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%